Changes of Radial Diffusivity and Fractional Anisotopy in the Optic Nerve and Optic Radiation of Glaucoma Patients - Tobias Engelhorn; Georg Michelson; Simone Waerntges; Marlen Otto; Ahmed El-Rafei; Tobias Struffert; Arnd Doerfler (The Scientific World Journal)
Purpose of this study was to evaluate with diffusion-tensor imaging (DTI) changes of radial diffusivity (RD) and fractional anisotropy (FA) in the optic nerve (ON) and optic radiation (OR) in glaucoma and to determine whether changes in RD and FA correlate with disease severity. Therefore, glaucoma patients and controls were examined using 3T. Regions of interest were positioned on RD and FA maps, and mean values were calculated for ON and OR and correlated with optic nerve atrophy and reduced spatial-temporal contrast sensitivity (STCS) of the retina. We found, that RD in glaucoma patients was significantly higher in the ON (0.74 ± 0.21 versus 0.58 ± 0.17⋅10−3 mm2 s−1; P<0.05) and OR (0.79 ± 0.23 versus 0.62 ± 0.14⋅10−3 mm2 s−1; P<0.05) compared to controls. Aside, FA was significantly decreased (0.48 ± 0.15 versus 0.66 ± 0.12 and 0.50 ± 0.20 versus 0.66 ± 0.11; P<0.05). Hereby, correlation between changes in RD/FA and optic nerve atrophy/STCS was observed (r>0.77). In conclusion, DTI at 3 Tesla allows robust RD and FA measurements in the ON and OR. Hereby, the extent of RD increase and FA decrease in glaucoma correlate with established ophthalmological examinations.